Parenting evidence-based programs (EBP): A study with Portuguese parents - Magalhães, Cátia (2016)
It is apparent that improving parent and child relations should be a major goal of any parental EBP. In other words, parents who care and support their children and have a good relationship and involvement are more willing to invest time in monitoring and supervision them and communicating their expectations that their children.